PTU-260 Are we working at a loss? Does routine coding for endoscopic retrograde cholangiopancreatography (ERCP) provide accurate remuneration?. (28th May 2012) - Jackson, V; Siadankay, L; Saleh, B; Sturgess, R; Stern, N
Abstract : Introduction: Endoscopic procedures in the UK are remunerated through "Payment by results" with a healthcare resource group (HRG) tariff assigned to each procedure. HRG tariffs depend on accurate coding of the diagnosis and procedure to enable appropriate payment from primary care trusts (PCT). There is little existing data about the accuracy of coding in ERCP to generate appropriate HRG tariffs. Methods: Cases were randomly selected from those attending for ERCP at our unit between 24 March 2010 and 2 July 2010 with full information available. Each procedure was reviewed by a member of the hospitals coding department and a consultant gastroenterologist who regularly performs ERCP, with details of initial routine coding available. Cases were all re-coded following clinician input with subsequent re-calculation of HRG tariff. Results: 39 cases were reviewed. 20 in-patient procedures and 19-day cases. This included 24 (61.5%) accurately coded and 15 (38.5%, 2-day cases and 7 in-patients) requiring re-coding. The re-coding was due to incorrect primary diagnostic code: 3; primary procedure code: 9; both codes: 3. Four of the procedure code changes resulted in increases to HRG tariffs. None of the re-coding led to a reduction in tariff. Three of these were due to incorrect coding of metal stent insertion and one due to omission of coding for sphincterotomy. The initial coding led to an income of £60 033 with the revised coding suggesting remuneration should have been £69 037: a shortfall of £9004. The single biggest shortfall was in the coding of "stent" insertion. Unless clearly labelled as "metal stent, " these were routinely coded as plastic stents which carry a lower tariff. Conclusion: There is a difference in coding of ERCPs in 38.5% of procedures we studied. This led to over 10% re-coded to a higher HRG tariff, potentially increasing ERCP related income. Accurate coding is necessary to ensure appropriate remuneration for hospital trusts. Particular attention to the recording of insertion and coding of metallic stents is needed. Competing interests: None declared. Reference: 1. Moar K, Rogers S. Impact of coding errors on departmental income: an audit of coding of microvascular free tissue transfer cases using OPCS-4 in UK. Br J Oral Maxillofac Surg 2012;50 :85–7.